Effects of supplemental mixed bile acids on growth performance, body composition, digestive enzyme activities, skin color, and flesh quality of juvenile large yellow croaker (Larimichthys crocea) in soybean oil based diet - Li, Jinbao; Wang, Zhen; Cao, Xiufei; Wang, Jianmin; Gong, Ye; Wang, Xiuneng; Lai, Wencong; Bu, Xianyong; Zheng, Jichang; Mai, Kangsen; Ai, Qinghui (Frontiers in Marine Science, 2023)
Now the replacement of fish oil (FO) with vegetable oils (VOs) has been broadly applied in aquatic feed, but studies reported that there were negative effects on growth, skin color, flavor and muscle texture. A 10-week feeding trial was conducted to investigate the effects of dietary mixed bile acids (BA) on growth performance, body composition, digestive enzyme activities, skin color and flesh quality of juvenile large yellow croaker (initial weight, 13.10 ± 0.18 g). Four iso-nitrogenous and iso-lipidic experimental diets were formulated and designated as soybean oil (SO), SO supplemented with 300 (BA300), 600 (BA600), and 1200 (BA1200) mg/kg bile acids. Two hundred and forty fish were randomly allocated into 12 floating net cages (1 m × 1 m × 1.5 m) that were located at marine fishing rafts. Each diet was randomly distributed in triplicate (three replicates per treatment, 20 fish per replicate). Fish were hand-fed to apparent satiation twice daily (05:30 and 17:30) for 10 weeks. Results showed that specific growth rate presented quadratic pattern with supplemental bile acids level, peaking at BA600 group. Meanwhile, feed conversion rate of cultured fish was significantly improved in BA600 group (P < 0.05). The redness (a*) of dorsal and lateral line skin and the yellowness (b*) of abdominal skin showed significantly quadratic pattern with the increase of supplemental BA level (P < 0.05), peaking at BA600 group. In terms of dorsal muscle texture, springiness showed a decreasing trend in significantly linear pattern with the increase of supplemental BA level, bottoming at BA600 group. However, cohesiveness and gumminess were significantly linear increased with the increase of supplemental BA level (P < 0.05). No significant differences were observed in lipase, amylase, and trypsin activities (P > 0.05). Total proportion of muscle n-3LCPUFA showed a linearly increasing trend with the increase of supplemental BA level. Muscle TG content was linearly increased with the increase of supplemental BA level (P < 0.05), and significant differences occurred as compared to fish fed diets with SO when supplemental BA level were reached 600 mg/kg and 1200 mg/kg (P < 0.05). The gene expression of acyl-CoA oxidase (aco) was significantly decreased in fish fed diets supplemented with 600 mg/kg bile acids compared with 300 mg/kg other than those fed diets with SO. In conclusion, these results suggested that mixed bile acids supplemented to SO-based diets could improve feed conversion ratio, skin color and flesh quality to some extent.